A Bibliometric Review of Sustainable Agriculture in Rural Development - Rusdiyana, Eksa; Sutrisno, Eko; Harsono, Iwan (Westscience Press, 2024)
This bibliometric review investigates the scholarly landscape of sustainable agriculture in the context of rural development, spanning from 1986 to 2024. With a comprehensive analysis of 980 publications, the study examines key themes, influential works, and emerging trends in the field. Through bibliometric techniques such as co-citation analysis and network visualization, the research identifies clusters of research topics, including technological advancements, social dimensions, economic impacts, and environmental considerations. Notable contributions by influential authors are highlighted, shedding light on critical issues such as rural livelihoods, participatory approaches, and alternative food networks. Furthermore, the study provides insights into the evolution of research interests over time, revealing emerging areas for future exploration. The findings contribute to a deeper understanding of sustainable agriculture's role in rural development and offer valuable insights for policymakers, practitioners, and researchers seeking to promote sustainable practices and enhance rural well-being.